Investimentos privados em infraestrutura nas economias emergentes: A importância do ambiente regulatório na atraç\~ao de investimentos - Katia Rocha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The objective of this study is to analyze the response of improvements in the regulatory rankings of emerging economies to private investments in infrastructure especially for Brazil. The proposed methodology relies on a fixed-effect panel model. We further investigated whether, after the 2008 global crisis, there was a significant change in the perception of the private investor in relation to the regulatory and institutional characteristics of emerging markets. The study covers eighteen emerging economies - Argentina, Brazil, China, Chile, Colombia, India, Indonesia, Malaysia, Mexico, Pakistan, Peru, Philippines, Russia, South Africa, Thailand, Turkey, Uruguay and Vietnam, which represented around 89% of private investment flow to emerging countries and totaled US 1.3 trillion and 4.480 projects for emerging countries in the period of 2000-2018. The results are significant with the expected signal. The better the country's regulatory quality ranking, the greater the volume of investments and the number of projects with private participation in infrastructure. The result is robust to several specifications and institutional characteristics added to the model. Finally, after the global crisis, model suggests there was a significant increase in the importance of the regulatory framework for decision-making and private capital allocation in this sector in emerging economies. If Brazil improves its position in the regulatory quality ranking to the same level occupied in mid-2000 (65th place, Colombia's current position in 2018), this would lead to an increase of 0.81% of gross domestic product (GDP) in investments. If it reaches the Chilean levels (89th place), the increase would be 1.59% of GDP. Such value added to the current levels would total 3.4% of GDP, value somehow closer to the target of 4.25% of GDP estimated by the World Bank for a sustained growth.
Keywords: G38; L51; F21; 330; infrastructure investments; emerging economies; regulation